2022
DOI: 10.1155/2022/5450575
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Nursing Practice Model in Case Management of Concurrent Chemotherapy and Radiochemotherapy Treatment in Cervical Cancer

Abstract: Objective. To construct a case management model of synchronous radiotherapy and concurrent chemotherapy and radiochemotherapy (CRR) for cervical cancer led by nurses and carry out preliminary implementation and evaluation, so as to explore a new model of nursing practice. Methods. Totally 80 cervical cancer patients were included in this study, 43 patients were in the experimental group, and 37 patients were in the control group. The clinical data, side effects, psychological reactions, and nutritional indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Weak 21. China, 2022 [ 37 ] QE 60 60 50.24 ± 6.49 49.42 ± 6.49 Squamous carcinoma Adenocarcinoma Adenosquamous carcinoma During comprehensive anti-cancer treatment Whole-course high-quality care (Before, During and after comprehensive treatment) combined with network continuation care interventions (Using WeChat). Provider- Team of medical and nursing staffs Conventional care interventions ( verbal health education about cervical cancer; they were informed of the precautions and examination items during surgery and radiotherapy; they were advised to complete daily basic care; they were strictly supervised to take medication and receive treatment on time; the hygiene and room temperature of wards and treatment rooms were maintained; and the changes of patients’ vital signs were strictly monitored and recorded) Total session, frequency and duration not mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weak 21. China, 2022 [ 37 ] QE 60 60 50.24 ± 6.49 49.42 ± 6.49 Squamous carcinoma Adenocarcinoma Adenosquamous carcinoma During comprehensive anti-cancer treatment Whole-course high-quality care (Before, During and after comprehensive treatment) combined with network continuation care interventions (Using WeChat). Provider- Team of medical and nursing staffs Conventional care interventions ( verbal health education about cervical cancer; they were informed of the precautions and examination items during surgery and radiotherapy; they were advised to complete daily basic care; they were strictly supervised to take medication and receive treatment on time; the hygiene and room temperature of wards and treatment rooms were maintained; and the changes of patients’ vital signs were strictly monitored and recorded) Total session, frequency and duration not mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the stages of cancer, two studies included stage Ia–IIb cervical cancer [ 25 , 48 ], two studies included stage I-II cervical cancer [ 6 , 39 ], two studies included stage I-IV cervical cancer [ 30 , 47 ], two studies included stage Ib2-IIb cervical cancer [ 38 , 45 ], four studies included pathological subtype (squamous carcinoma, adenocarcinoma, adenosquamous carcinoma) of cervical cancer [ 23 , 37 , 43 , 44 ] and three studies’ stages of cancer not mentioned [ 31 , 34 , 41 ] and another eleven studies were ranges from I- IV B1 remaining studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have suggested that a case management model may be useful in increasing engagement in and the efficacy of self-care among patients undergoing radiotherapy. 53 Others suggested that e-health devices are preferable. 23 , 26 , 49 Several studies have shown that patients have difficulties initiating communication about self-care strategies with healthcare practitioners and that this is a source of dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%